Sintered expanded graphite shaped molten salt energy storage material and preparation method thereof

By asphalt sintering expanded graphite and recombining it with high-temperature molten salt, the problems of expanded graphite settlement, segregation and molten salt separation in applications are solved, the thermal conductivity and strength of the material are improved, and molten salt leakage is prevented.

CN119529775AActive Publication Date: 2025-02-28ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411721612.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

The existing expanded graphite, porous graphite and high-temperature molten salt have problems such as sedimentation, segregation, molten salt separation and poor thermal conductivity in applications.

Method used

By using asphalt to shape and sinter the expanded graphite and combining high-temperature molten salt to form a composite material, the problems of sedimentation, segregation and molten salt separation are solved, and thermal conductivity is improved.

Benefits of technology

The sintered expanded graphite has achieved good strength retention ability at room temperature, and the overall material has excellent strength and good thermal conductivity, while preventing the leakage of molten salt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119529775A_ABST
    Figure CN119529775A_ABST
Patent Text Reader

Abstract

The invention discloses a sintered expanded graphite shaped molten salt energy storage material and a preparation method thereof. The energy storage material is mainly formed by compounding sintered expanded graphite and fused salt, the sintered expanded graphite is a carrier of the fused salt, the mass of the sintered expanded graphite accounts for 35-45% of the total mass of the sintered expanded graphite shaped fused salt energy storage material, the mass of the fused salt accounts for 55-65% of the total mass of the sintered expanded graphite shaped fused salt energy storage material, and the fused salt is high-temperature fused salt. The high-temperature fused salt comprises one or a combination of more of sodium chloride, sodium fluoride, magnesium chloride, calcium chloride and potassium chloride, and the sintered expanded graphite is mainly prepared from a mixture of asphalt, a dispersing agent, expanded graphite and adjusting components through drying, pressure forming, drying and sintering in sequence. The adjusting component accounts for 1-5% of the total mass of the sintered expanded graphite shaped molten salt energy storage material. The sintered expanded graphite shaped molten salt provided by the invention is good in energy storage and heat conduction performance, low in heat loss, good in corrosion resistance, high in strength and capable of preventing leakage of the molten salt, so that the sintered expanded graphite shaped molten salt has good safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a sintered expanded graphite shaped molten salt energy storage material and a preparation method thereof. Background Art

[0002] Molten salt energy storage technology is a thermal energy storage technology that uses molten salt as a heat storage medium. This technology can effectively store and release a large amount of thermal energy and is widely used in solar thermal power generation, industrial waste heat recovery, and central heating systems. It has the advantages of high heat storage density, wide temperature range, low cost, long life, and environmental friendliness. However, molten salts usually have disadvantages such as low thermal conductivity and strong corrosion properties of some molten salts at high temperatures.

[0003] Expanded graphite is a loose and porous worm-like substance with a large number of network-like microporous structures. Its large specific surface area and high surface activity give it good adsorption, coating and thermal conductivity properties, and it has a wide range of applications in energy storage and other fields. However, there are phenomena of sedimentation, segregation and molten salt separation of expanded graphite in phase change materials.

[0004] Compared with expanded graphite, porous graphite materials have the advantages of light weight, good thermal conductivity, good corrosion resistance, good heat resistance and good processability, and are widely used in the automotive industry, aerospace, energy storage, medical, electronics industry and communications. However, when the prior art uses asphalt as a binder for porous graphite products, it usually has the following characteristics:

[0005] On the one hand, the role of asphalt binder comes from the residue after asphalt calcination and carbonization that bonds the solid filler together. During the sintering process, about 50% of the light components of the asphalt volatilize, and it is the residue after asphalt roasting that plays a bonding role.

[0006] On the other hand, asphalt tends to become brittle at room temperature and has unstable bonding properties, and the porous graphite products obtained from it have poor strength retention capabilities at room temperature. Summary of the invention

[0007] In order to improve the problems existing in the existing expanded graphite, porous graphite and high-temperature molten salt, the present invention provides a sintered expanded graphite shaped molten salt energy storage material and a preparation method. The preparation method of the present invention solves the sedimentation, segregation and molten salt separation problems in the actual application of expanded graphite by using asphalt to shape and sinter the expanded graphite, and the molten salt is compounded with the sintered expanded graphite skeleton material. The sintered expanded graphite has good strength retention ability at room temperature, so that the composite material as a whole has excellent strength and good thermal conductivity, and can also prevent the leakage of molten salt.

[0008] In order to solve the above technical problems, the following technical solutions are adopted:

[0009] 1. A sintered expanded graphite shaped molten salt energy storage material

[0010] The sintered expanded graphite shaped molten salt energy storage material is mainly composed of sintered expanded graphite and molten salt, and the sintered expanded graphite is used as a carrier of the molten salt.

[0011] The masses of the sintered expanded graphite and the molten salt account for 35-45% and 55-65% of the total mass of the sintered expanded graphite shaped molten salt energy storage material respectively.

[0012] The molten salt is a high-temperature molten salt, and the high-temperature molten salt includes a combination of one or more of sodium chloride, sodium fluoride, magnesium chloride, calcium chloride and potassium chloride.

[0013] The sintered expanded graphite contains an adjustment component, and the mass ratio of the adjustment component to the sintered expanded graphite is 1-5:35-45, that is, the mass of the adjustment component accounts for 1-5% of the total mass of the sintered expanded graphite shaped molten salt energy storage material, and the adjustment component is a combination of one or more of silicon carbide, chopped carbon fiber and phenolic resin. The length of the chopped carbon fiber is 1-100 mm.

[0014] Furthermore, the sintered expanded graphite is mainly prepared by drying, pressurizing, drying and sintering a mixture of asphalt, dispersant, expanded graphite and adjusting components in sequence; the mass ratio of the asphalt to the dispersant is 2.5 to 3.5:1; the mass ratio of the asphalt to the expanded graphite is 5 to 20:1; the mass ratio of the expanded graphite to the adjusting components is 1 to 15:1.

[0015] Furthermore, the porosity of the sintered expanded graphite is 50% to 70%, that is, the volume ratio of the sintered expanded graphite to the molten salt is 30-50:50-70.

[0016] 2. A method for preparing sintered expanded graphite shaped molten salt energy storage material

[0017] The preparation method comprises the following steps:

[0018] 1) Mix asphalt particles, dispersant, expanded graphite and adjustment components to obtain an expanded graphite-asphalt mixture. The step 1) is specifically as follows: pre-screen the asphalt particles through a 100-mesh screen and retain fine particles, screen the expanded graphite through a 100-mesh screen and retain coarse particles, mix the sieved asphalt particles and dispersant in a mass ratio of 2.5 to 3.5:1, add the sieved expanded graphite and adjustment components in a ratio of 5 to 20:1 for the mass ratio of asphalt particles to expanded graphite and 1 to 15:1 for the mass ratio of expanded graphite to adjustment components, and fully stir at a speed of 100 to 150 r / min to obtain the expanded graphite-asphalt mixture. In this process, by reasonably controlling the stirring rate, it is helpful to prevent the agglomeration of expanded graphite powder and adjustment components.

[0019] Specifically, the preparation process of the asphalt particles is as follows: after the asphalt is ground by a grinder, it is passed through a 100-mesh sieve to remove some coarse particles to obtain the asphalt particles.

[0020] Specifically, the asphalt is a combination of one or more of medium-temperature asphalt, modified asphalt, and high-temperature asphalt.

[0021] Specifically, the material of the dispersant is one or more of ethanol, toluene and quinoline.

[0022] 2) After drying the expanded graphite-asphalt mixture, transfer it to a mold, and obtain a molded block by pressure molding, and obtain an embryo after the molded block is dried; in the step 2), the drying process is: drying at 60°C to 90°C for 2 to 5 hours and then naturally cooling, and stopping stirring during the drying stage and the natural cooling stage; the pressure of the pressure molding is 10Mpa, and after the pressure molding, the strength of the embryo is increased, which helps the asphalt to connect with each other to form a heat conduction network during the sintering process; the drying conditions are: drying at an ambient temperature of 50 to 100°C for 1 to 2 hours.

[0023] 3) Sintering the embryo to obtain sintered expanded graphite; in the step 3), the specific process of sintering is: heating and heating in an inert gas atmosphere, the temperature is raised from 50°C to 400°C, and the heating rate is 1.2-1.5°C / h; keeping warm at 400°C for 30 minutes; the temperature is raised from 400°C to 900-1400°C, and the heating rate is 1.5-2°C / min; after heating to the required temperature and keeping warm for 2 hours, the temperature is lowered to 50-200°C, and the cooling rate is 1.5-2°C / min. During the sintering process, the escape rate of the light components inside the asphalt is controlled by adjusting the heating and cooling rate, so as to meet the structural requirements of the sintered expanded graphite.

[0024] In this step, the porosity of the sintered expanded graphite obtained by sintering is 50-70%.

[0025] 4) A eutectic salt is prepared using a molten salt, and the eutectic salt is compounded onto the sintered expanded graphite using a vacuum impregnation method to obtain the sintered expanded graphite shaped molten salt energy storage material. In the step 4), the conditions of the vacuum impregnation method are: immersing the sintered expanded graphite in the molten eutectic salt, maintaining the vacuum pressure at -0.08atm, and the temperature is greater than the eutectic point of the eutectic salt. Appropriate vacuum helps the molten eutectic salt to fully fill the sintered expanded graphite and increase the energy storage density.

[0026] Furthermore, in step 4), the specific process of using the molten salt material to prepare the eutectic salt is: after drying and grinding the molten salt material, the obtained powder is melted and cooled at a temperature above the eutectic point to obtain the eutectic salt. The molten salt is one or a combination of sodium chloride, sodium fluoride, magnesium chloride, calcium chloride and potassium chloride.

[0027] In the present invention, the "high-temperature molten salt" refers to an inorganic salt composed of halides, nitrates, sulfates, etc. of alkali metals and alkaline earth metals that can melt at a temperature of 300°C or above, that is, "high-temperature molten salt" refers to a molten salt with an operating temperature greater than or equal to 300°C.

[0028] In the present invention, the inert gas is any one of nitrogen, helium, neon, argon, krypton and radon, or a combination of two or more thereof.

[0029] The beneficial effects of the present invention are as follows:

[0030] 1. The method of the present invention improves the problem of poor thermal conductivity of high-temperature molten salt energy storage materials. The 3D network porous structure formed by asphalt and expanded graphite after high-temperature sintering makes the energy storage material of the present invention have better heat transfer performance, so the heat transfer efficiency is further improved, and the application ability of high-temperature molten salt energy storage materials is improved, thereby obtaining huge economic benefits.

[0031] 2. The method of the present invention strictly controls the fineness of the raw materials, thereby increasing the specific surface area of ​​the raw materials, and strictly controls the sintering temperature in multiple stages, so that the obtained sintered expanded graphite has good porosity and excellent flexural strength, further improving the safety performance of high-temperature molten salt energy storage materials during transportation and use.

[0032] 3. The sintered expanded graphite obtained by the present invention has good environmental adaptability, excellent corrosion resistance, and a wide applicable temperature range, which expands the application range of the sintered expanded graphite in high-temperature molten salt energy storage materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is a schematic diagram of the preparation process of the sintered expanded graphite shaped molten salt energy storage material provided by the present invention;

[0034] Figure 2 This is a microscopic morphology of the sintered expanded graphite shaped molten salt energy storage material obtained in Examples 1 to 3 of the present invention;

[0035] Figure 3 These are the actual pictures of Example 1 of the present invention and Comparative Example 2 before and after 100 cycles. DETAILED DESCRIPTION

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings and other implementation methods can be obtained based on these drawings without creative work.

[0037] To simplify the drawings, each drawing schematically shows only the parts related to the invention, which do not represent the actual structure of the product.

[0038] It should be further understood that the term "and / or" used in the present description and the appended claims refers to any and all possible combinations of one or more of the associated listed items, and includes these combinations.

[0039] The first aspect of the present invention provides a sintered expanded graphite shaped molten salt energy storage material. The energy storage material of the present invention has excellent thermal conductivity and good flexural strength at room temperature, thereby reducing heat loss during the application of the energy storage material and saving the use cost. In addition, this sintered expanded graphite shaped molten salt energy storage material has excellent corrosion resistance and good strength, prevents the leakage of molten salt, and improves the safety of high-temperature molten salt application. The energy storage material of the present invention fixes the expanded graphite in a sintered asphalt skeleton after high-temperature sintering, and uses the obtained sintered expanded graphite as a substrate to prepare the sintered expanded graphite shaped molten salt energy storage material. The sintered expanded graphite can further prevent the leakage of molten salt, and finally overcomes the sedimentation, segregation and molten salt separation problems of expanded graphite in the actual application process.

[0040] The second aspect of the present invention provides a method for preparing a sintered expanded graphite shaped molten salt energy storage material. The specific steps are as follows: Figure 1 The preparation method of the present invention realizes the effective combination of sintered expanded graphite and high-temperature molten salt through the reaction process of high-temperature sintering and vacuum impregnation. The preparation method of the present invention also provides the preferred raw material fineness and stable sintering heating rate according to the above raw material combination.

[0041] The preparation method of the present invention is simple, greatly saves equipment costs, and greatly improves the cost performance of the product

[0042] The specific embodiments of the present invention are as follows:

[0043] Example 1

[0044] In this embodiment, medium-temperature asphalt is obtained in advance as a binder, ethanol is used as a dispersant, phenolic resin is used as an adjustment component, and a high-temperature molten salt including 48wt% of sodium chloride and 52wt% of magnesium chloride (the eutectic point of this high-temperature molten salt is 450°C) is prepared based on the above materials. Figure 1 As shown, the preparation method comprises the following steps:

[0045] 1) Grind the medium-temperature asphalt with a grinder, pass through a 100-mesh sieve, and take the fine particle part to obtain asphalt particles. Pass the expanded graphite through a 100-mesh sieve and retain the coarse particle part. After the asphalt particles and ethanol are fully mixed in a mass ratio of 3:1, the expanded graphite and the adjustment components are added in a ratio of 10:1 of the mass ratio of asphalt particles to expanded graphite and 10:1 of the mass ratio of expanded graphite to phenolic resin, and the mixture is mixed and stirred at a speed of 120 r / min to obtain an expanded graphite-asphalt mixture.

[0046] 2) drying the expanded graphite-asphalt mixture at 70° C. for 3 h, cooling it naturally, transferring it to a mold, and press-molding it at 10 MPa, taking out the molded block from the mold, and then transferring the molded block to an oven, and drying it at an ambient temperature of 80° C. for 1 h to obtain an embryo;

[0047] 3) Sintering the embryo to obtain sintered expanded graphite; the specific process of sintering is: first heating and heating the temperature from 50°C to 400°C at a heating rate of 1.2°C / h; keeping the temperature at 400°C for 30 minutes; heating the temperature from 400°C to 1000°C at a heating rate of 1.7°C / min; heating to 1100°C and keeping the temperature for 2 hours, then cooling down to 200°C at a cooling rate of 2°C / min; the reaction environment is a nitrogen atmosphere.

[0048] In the sintered expanded graphite obtained in this embodiment, the mass ratio of the sintered expanded graphite to the adjustment component is 45:1.

[0049] 4) Dry the sodium chloride and anhydrous magnesium chloride in an oven at 130°C for 2 hours and grind them in a mortar for 30 minutes. Place the dried mixed powder in a reactor with a pressure of 2.5Mpa and nitrogen protection, heat it to 580°C at a heating rate of 4°C / min, and keep it warm for 4 hours, and finally cool it naturally to room temperature to form a sodium chloride-magnesium chloride eutectic salt. Immerse the sintered expanded graphite in the molten eutectic salt, and compound the eutectic salt onto the sintered expanded graphite matrix by vacuum impregnation at -0.08atm and 525°C to obtain an expanded graphite shaped molten salt energy storage material.

[0050] Example 2

[0051] In this embodiment, except for the following differences, other steps and conditions are the same as those in Example 1: In this embodiment, modified asphalt is used as a binder, and a combination of chopped carbon fibers and phenolic resin is used as an adjustment component. In step 1), the mass ratio of asphalt particles to expanded graphite is 5:1, the ratio of expanded graphite to chopped carbon fibers is 15:1, and the mass ratio of expanded graphite to phenolic resin is 5:1.

[0052] In the sintered expanded graphite obtained in this embodiment, the mass ratio of the sintered expanded graphite to the adjustment component is 35:1.3.

[0053] Example 3

[0054] In this embodiment, except for the following differences, other steps and conditions are the same as those in Example 1: In this embodiment, a combination of medium-temperature asphalt and high-temperature asphalt is used as a binder, and the mass ratio between the medium-temperature asphalt and the high-temperature asphalt is 3:1, and a combination of chopped carbon fibers and phenolic resin is used as an adjustment component. In step 1), the mass ratio of asphalt particles to expanded graphite is 5:1, the ratio of expanded graphite to chopped carbon fibers is 15:1, and the mass ratio of expanded graphite to phenolic resin is 5:1.

[0055] In the sintered expanded graphite obtained in this embodiment, the mass ratio of the sintered expanded graphite to the adjustment component is 35:1.

[0056] Comparative Example 1

[0057] In this comparative example, sodium chloride-magnesium chloride eutectic salt was prepared by the following process: sodium chloride and anhydrous magnesium chloride were dried in an oven at 130°C for 2h, then mixed in a mass ratio of 48:52, and ground in a mortar for 30min. The dried mixed powder was placed in a reactor with a pressure of 2.5Mpa and nitrogen protection, heated to 580°C at a heating rate of 4°C / min, and kept warm for 4h, and finally naturally cooled to room temperature to form sodium chloride-magnesium chloride eutectic salt.

[0058] Comparative Example 2

[0059] In this comparative example, a composite phase change material of expanded graphite and sodium chloride-magnesium chloride eutectic salt was prepared by the following process: sodium chloride and anhydrous magnesium chloride were dried in an oven at 130°C for 2h, then mixed in a mass ratio of 48:52, and ground in a mortar for 30min. The dried mixed powder was placed in a reactor with a pressure of 2.5Mpa and nitrogen protection, heated to 580°C at a heating rate of 4°C / min, and kept warm for 4h, and finally naturally cooled to room temperature to form sodium chloride-magnesium chloride eutectic salt.

[0060] The volume ratio of expanded graphite and high-temperature molten salt is 43:57 (the porosity of the material obtained in Example 1 is set so that the volume ratio of expanded graphite and high-temperature molten salt in this comparative example is equal to the volume ratio of sintered expanded graphite and high-temperature molten salt in Example 1), and the high-temperature molten salt is compounded into the expanded graphite by vacuum impregnation under the conditions of -0.08atm and 525°C.

[0061] The thermal conductivity and flexural strength of the products obtained in the comparative examples and embodiments of the present invention, as well as the porosity of the sintered expanded graphite obtained in each embodiment are shown in the following table:

[0062]

[0063] As can be seen from the above table, the sintered expanded graphite obtained by the method of the present invention has a stable and good porosity. Compared with the eutectic salt obtained in Comparative Example 1, the energy storage material obtained by the method of the present invention has a higher thermal conductivity and a stronger flexural strength. Compared with the material obtained in Comparative Example 2, the flexural strength of the energy storage material obtained by the method of the present invention is greatly increased.

[0064] The microscopic morphology of the sintered expanded graphite shaped molten salt energy storage material obtained in Examples 1 to 3 of the present invention is shown in FIG. Figure 2 As shown, it can be seen that in the sintered expanded graphite shaped molten salt energy storage material obtained by the method of the present invention, the high-temperature molten salt particles, the adjusted components and the sintered expanded graphite frame have good adhesion.

[0065] The materials obtained in Example 1 and Comparative Example 2 of the present invention were subjected to cycle tests. In the cycle tests, the temperature control program of each cycle was to increase the temperature from room temperature to 500°C at a heating rate of 20°C / min. After reaching 500°C, the heating was stopped and the furnace was cooled to room temperature. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the sintered expanded graphite material of the present invention overcomes the sedimentation, segregation and molten salt separation problems of expanded graphite during long-term application compared with the expanded graphite used in Comparative Example 2.

[0066] It should be noted that the present invention is not limited to the specific technical solutions of the above embodiments. In addition to the above embodiments, the present invention may also have other implementation schemes. All technical solutions formed by equivalent replacement are within the protection scope required by the present invention.

Claims

1. A sintered expanded graphite shaped molten salt energy storage material, characterized in that: The sintered expanded graphite shaped molten salt energy storage material is mainly composed of sintered expanded graphite and molten salt, and the sintered expanded graphite is used as a carrier of the molten salt.

2. The sintered expanded graphite shaped molten salt energy storage material according to claim 1, characterized in that: The masses of the sintered expanded graphite and the molten salt account for 35-45% and 55-65% of the total mass of the sintered expanded graphite shaped molten salt energy storage material respectively.

3. The sintered expanded graphite shaped molten salt energy storage material according to claim 1, characterized in that: The molten salt is a high-temperature molten salt, and the high-temperature molten salt includes a combination of one or more of sodium chloride, sodium fluoride, magnesium chloride, calcium chloride and potassium chloride; and / or the porosity of the sintered expanded graphite is 50% to 70%.

4. The sintered expanded graphite shaped molten salt energy storage material according to claim 1, characterized in that: The sintered expanded graphite contains an adjustment component, and the mass ratio of the adjustment component to the sintered expanded graphite is 1-5:35-45. The adjustment component is a combination of one or more of silicon carbide, chopped carbon fiber and phenolic resin.

5. The sintered expanded graphite shaped molten salt energy storage material according to claim 4, characterized in that: The sintered expanded graphite is mainly prepared by drying, pressurizing, drying and sintering a mixture of asphalt, dispersant, expanded graphite and adjusting components in sequence; the mass ratio of the asphalt to the dispersant is 2.5 to 3.5:1; the mass ratio of the asphalt to the expanded graphite is 5 to 20:1; the mass ratio of the expanded graphite to the adjusting components is 1 to 15:

1.

6. A method for preparing the sintered expanded graphite shaped molten salt energy storage material according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) mixing asphalt particles, a dispersant, expanded graphite and an adjustment component to obtain an expanded graphite-asphalt mixture; 2) drying the expanded graphite-asphalt mixture, transferring it to a mold, and press-molding it to obtain a molded block, and drying the molded block to obtain an embryonic body; 3) sintering the embryo to obtain sintered expanded graphite; 4) using molten salt to prepare eutectic salt, and using vacuum impregnation method to compound the eutectic salt onto sintered expanded graphite to obtain the sintered expanded graphite shaped molten salt energy storage material.

7. The preparation method according to claim 6, characterized in that: The step 1) is specifically as follows: pre-passing the asphalt particles through a 100-mesh sieve and retaining fine particles, passing the expanded graphite through a 100-mesh sieve and retaining coarse particles, mixing the asphalt particles and the dispersant in a mass ratio of 2.5 to 3.5:1, adding the expanded graphite and the adjusting component in a ratio of 5 to 20:1 of the mass ratio of the asphalt particles to the expanded graphite and 1 to 15:1 of the mass ratio of the expanded graphite to the adjusting component, and fully stirring at a speed of 100 to 150 r / min to obtain the expanded graphite-asphalt mixture.

8. The preparation method according to claim 6, characterized in that: In the step 2), the drying process is: drying at 60°C to 90°C for 2 to 5 hours and then naturally cooling; the pressure of the press molding is 10Mpa; and the drying conditions are: drying at an ambient temperature of 50 to 100°C for 1 to 2 hours.

9. The preparation method according to claim 6, characterized in that: In the step 3), the specific process of sintering is: heating in an inert gas atmosphere, the temperature is raised from 50°C to 400°C, and the heating rate is 1.2-1.5°C / h; keeping warm at 400°C for 30 minutes; the temperature is raised from 400°C to 900-1400°C, and the heating rate is 1.5-2°C / min; keeping warm for 2 hours, and cooling to 50-200°C, and the cooling rate is 1.5-2°C / min.

10. The preparation method according to claim 6, characterized in that: In the step 4), the conditions of the vacuum impregnation method are: the vacuum pressure is -0.08atm, and the temperature is greater than the eutectic point of the eutectic salt.

Citation Information

Patent Citations

  • High-thermal conductivity inorganic salt / expandable graphite / graphite flake block composite phase-change material and preparation and application thereof

    CN107488440A

  • Carbon-based phase-change energy storage material and preparation method thereof

    CN109233751A

  • Assembly method of expanded graphite reinforced heat conduction ceramic-based shaped high-temperature phase change heat storage element and heat storage element formed by assembly method

    CN111793474A

  • Method for producing a latent heat storage material

    US20100116457A1